APLIKASI PETA PIKIRAN (MIND MAPP) DALAM IPA UNTUK MERANGSANG KREATIVITAS SISWA SEKOLAH DASAR - Shanta Rezkita (Universitas Sarjanawiyata Tamansiswa, 2014)
This article presents an overview of the application of mind map in science learning in elementary school. Mind maps help teachers and students in summarizing material science. The use of colors, images, keywords or short sentences on the mind map is able to stimulate the creativity of students. Creativity leads to thinking creatively here. When creating a mind map, students connect some important concepts in science-related topics. Thus a balance exists between the functions of the right brain with the left brain. In addition, students are also involved in the manufacture of divergent ideas based on the theme then through a process of convergent thinking students can find solutions related to the theme. f the dimension is associated with learning, teachers can stimulate students' creativity by stimulating their thinking abilities (cognitive dimension), foster an attitude and an interest in making a mind map (affective dimension) and provide the facilities and infrastructure to create mind maps (psychomotor dimension) .